2022
DOI: 10.3389/fpsyt.2022.859322
|View full text |Cite
|
Sign up to set email alerts
|

MR-Spectroscopy of GABA and Glutamate/Glutamine Concentrations in Auditory Cortex in Clinical High-Risk for Psychosis Individuals

Abstract: Psychosis involves changes in GABAergic and glutamatergic neurotransmission in auditory cortex that could be important for understanding sensory deficits and symptoms of psychosis. However, it is currently unclear whether such deficits are present in participants at clinical high-risk for psychosis (CHR-P) and whether they are associated with clinical outcomes. Magnetic Resonance Spectroscopy (MEGAPRESS, 1H-MRS at 3 Tesla) was used to estimate GABA, glutamate, and glutamate-plus-glutamine (Glx) levels in audit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The use of Glx/GABA+ as a proxy measure of E/I neurotransmission is supported by a study that observed a regional balance between Glx and GABA+ at 3T (Steel et al, 2020). Further, the Glx/GABA+ ratio has been employed in prior studies of visual (Takei et al, 2016; L. Zhang et al, 2020), cingulate (Bezalel et al, 2019), frontal (Liu et al, 2015) and auditory cortex (Grent-’t-Jong et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of Glx/GABA+ as a proxy measure of E/I neurotransmission is supported by a study that observed a regional balance between Glx and GABA+ at 3T (Steel et al, 2020). Further, the Glx/GABA+ ratio has been employed in prior studies of visual (Takei et al, 2016; L. Zhang et al, 2020), cingulate (Bezalel et al, 2019), frontal (Liu et al, 2015) and auditory cortex (Grent-’t-Jong et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Further, the Glx/GABA+ ratio has been employed in prior studies of visual (Takei et al, 2016;L. Zhang et al, 2020), cingulate (Bezalel et al, 2019), frontal (Liu et al, 2015) and auditory cortex (Grent-'t-Jong et al, 2022).…”
Section: Mrs Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy functioning neurotypical individuals, the mechanism of efficient information transfer in neural circuits relies upon a balance of cortical inhibition and excitation (Haider et al, 2006). An interplay between the inhibitory GABAergic interneurons and the excitatory Glutamatergic synapses achieves inhibitory and excitation balance (Grent-'t-Jong et al, 2022;Whittington et al, 1995).…”
Section: Chapter 3: Magnetic Resonance Spectroscopy: Video Game Use A...mentioning
confidence: 99%